Hubungan Kreativitas dengan Kinerja Karyawan Era Industri 4.0 pada UMKM KUB Melati di Bangkalan - Siti Faizah Nuraini; Jayaning Sila Astuti (Journal of Social, Culture, and Language, 2024)
Between 2020-2030, Indonesia will experience a demographic bonus of a productive-age workforce of 70% of the total population (BPS, 2022). Ong and Mahazan (2022b) mentioned that the characteristics of the workforce in the 4.0 era are that it’s difficult to change their weakness so that they feel less suitable for work and company. However, KUB Melati MSME in Bangkalan, which consists of productive-age employees in the 4.0 era, is able to create thousands of creative products that are in demand by foreigners every year, making it the only Agel Rope MSME that has been able to maintain its existence in Madura to date. To determine the relationship between creativity and employee performance in the industrial era 4.0 at KUB Melati MSME in Bangkalan. Using a quantitative approach, data collection thechniques in the form of saturated sampling using a Likert Scale, and data analysis methods in the form of Product Moment Correlation test using SPSS 24.0 for windows. The correlation coefficient value is 0.74 with a significance of 0.000 (significance 0.05). There is a positive, significant and strong relationship between creativity and employee performance in the industrial era 4.0 at KUB Melati MSME in Bangkalan. Keywords: Creativity, employee performance, sustainable MSME.